Lumbar disc herniation reabsorption: a review of clinical manifestations, mechanisms, and conservative treatments - Chai, Yuan; Shen, Xuyu; Wang, Zixin; Zhang, Xiaoyun; Wang, Zhiqiang; Zuo, Xinchen; Liu, Jintao (Frontiers in Medicine, 2025)
Lumbar disc herniation (LDH) is a common and frequently occurring condition primarily caused by lumbar intervertebral disc degeneration (LIVDD) and protrusion of the nucleus pulposus (NP), with low back pain and lower limb pain as the main clinical manifestations. It is characterized by a prolonged disease course and a high recurrence rate, with patients often experiencing long-term suffering, significantly impairing their quality of life and mental health. Studies have found that some LDH patients, without undergoing surgery or chemonucleolysis, experience spontaneous shrinkage and resorption of the intervertebral disc (IVD) tissue, along with relief of back and leg pain-a phenomenon referred to as LDH reabsorption. Modern medical research suggests that this reabsorption process is closely related to factors such as inflammatory responses, macrophage activation, extracellular matrix enzyme balance, neovascularization, ferroptosis, mitochondrial function, oxidative stress, and cellular autophagy. However, the precise mechanisms of LDH reabsorption and commonly used clinical therapies remain unclear, leading to suboptimal treatment outcomes. This study systematically reviews the relevant literature on LDH reabsorption, focusing on clinical diagnosis, underlying mechanisms, and common therapeutic strategies, aiming to summarize recent research progress and provide theoretical references for future clinical prevention and treatment of LDH.